DITRUPA BREVIS N.SP., A NEW SERPULID FROM THE MEDITERRANEAN NEOGENE WITH COMMENTS ON THE ECOLOGY OF THE GENUS (Rivista italiana di Paleontologia e Stratigrafia, 1999)
The new species Ditrupa brevis (Polychaeta, Serpulidae) is described from Middle Pliocene silts of southern Italy. It is also reported from Late Miocene sediments of southern Italy. The associated faunas suggest an infralittoral or upper-circalittoral distribution. A morphometrical and microstructural analysis of tube was carried out. D. brevis closely resembles Ditrupa arietina but several morphometrical differences allow to discriminate the two species. The Ditrupa tubes provide a substrate for a diversified epifauna. Their high density greatly affects species composition and diversity of soft-bottom communities. It is concluded that Ditrupa can live in various positions with respect to the sediment surface, depending on local sedimentation rate and dynamics.